Barriers and opportunities for gender-responsive climate-smart agriculture adoption in Northern Uganda - Bamanyaki, Patricia A. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This Info Note discusses gender-based barriers to climate-smart agriculture adoption in Northern Uganda and the opportunities for gender-responsive climate-smart agriculture.